PENILAIAN EKSPRESI PROTEIN MDM2 DAN P53 SEBAGAI PREDIKTOR RESPON RADIOTERAPI PADA KANKER SERVIKS - Rahayu, Kun Mardiwati; Siregar, Budiningsih; Kurnia, Iin (Bioma, 2016)
Cervical cancer is the second most common malignancy in Indonesia, and most of cases were already in advanced stage where radiotherapy is a tratement to given. Apoptosis is one of the markers for survival assessment of therapeutic response. In animal experiments MDM2 expression in various cell types to act as a survival factor by inhibiting the apoptotic function of p53 that is played by apoptosis can lead to malignant transformation and result in resistance to radiotherapy. Therefore, MDM2 is overexpressed due to alleged damage to p53 can also be used to assess the success of radiotherapy. This study aimed to assess the expression of MDM2 and p53 immunohistochemistry in cervical cancer and its relation to radiotherapy response. This study is a retrospective cross-sectional descriptive. The sample consisted of 23 cases of advanced cervical cancer were biopsied, 17 cases with complete response to radiation and 6 cases of partial radiation response. This study showed complete radiotherapy group MDM2 expression was found in 70.59% (12 cases) and p53 expression was found in 94.11% (16 cases), while the expression of MDM2, a partial response was found in 100% (6 cases), while the expression p53 66.67% (4 cases). MDM2 and p53 expression with SPSS 16 chi square test showed no association with response to radiotherapy in cervical cancer.